A study of the variants of /r/ in Klang Valley Malay / Katherine Schmittauer - Katherine , Schmittauer (2024)
The Malay language has rich phonological variation based on geographic and social context. Previous research has identified /r/ as the consonant phoneme with greatest variation. This study aimed to combine perceptual and acoustic analysis to more accurately quantify the variants of /r/ used in the Klang Valley and to correlate the usage of these variants with social variables. Data collected consisted of speech recordings of two styles of speech and information about the speakers’ age, gender, educational and language background. Findings suggest that the variants of /r/ correlate with phonetic environment, age, gender, and language background. The study identified four rhotic variants including the tap [ɾ], trill [r], approximant [ɹ], and a zero-realization. The appearance of the approximant [ɹ], not previously documented in Peninsular Malay, possibly indicates a linguistic change in progress. The study was limited by the size of the sample and relative homogeneity of the speakers’ backgrounds.